Ecosystem Services for Well-Being in Deltas Integrated Assessment for Policy Analysis - Nicholls, Robert J.; Hutton, Craig W.; Adger, W. Neil; Hanson, Susan E.; Rahman, Md. Munsur; Salehin, Mashfiqus (Springer Nature, 2018)
Ecosystem services; Sustainable development; Environmental management; Natural resource management; Coastal management; Bangladesh and sea-level rise research; Governance of ecosystem services; Regional climate change in South Asia